Conceptualized of lexeme «war» in the novels by Oles Gonchar (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The lexico-semantic field of «war» in the works by O. Gonchar is analyzed in the article. Special attention is paid to the linguistic expression of a tragedy of war.
Keywords: war; lexeme; conceptualized; world-outlook contents; position; semantics